Single-nucleotide polymorphism profiling by multimodal-targeted next-generation sequencing in methotrexate-resistant and -sensitive human osteosarcoma cell lines - Casotti, Chiara; Hattinger, Claudia Maria; Patrizio, Maria Pia; Luppi, Silvia; Fantoni, Leonardo; Pasello, Michela; Scotlandi, Katia; Ibrahim, Toni; Serra, Massimo (Frontiers in Pharmacology, 2023)
Methotrexate (MTX) is one of the most important drugs included in first-line protocols to treat highgrade osteosarcoma (HGOS). Although several polymorphisms have been reported to be associated with drug response or MTX-related toxicity in pharmacogenetic studies their role in the development of MTX resistance in HGOS is still unclear. Therefore, in this study, 22 single nucleotide polymorphisms (SNPs) in four genes of the folate metabolism, seven MTX transporter genes, and two SNPs of the tumor protein p53 (TP53) gene were explored by a custom multimodal targeted next generation sequencing (mmNGS) approach in eight MTX-resistant and 12 MTX-sensitive human HGOS cell lines. The panel was validated by TaqMan genotyping assays. High instability around the TP53 rs1642785 was observed in all U-2OS/MTX variants. Allele changes of solute carrier family 19 member 1/replication factor C subunit 1 (SLC19A1, previously known as RFC1), rs1051266 were identified in all Saos-2/MTX-resistant variants in both DNA and RNA-derived libraries compared to the parental Saos-2 cell line. Differently, allele changes of the methylenetetrahydrofolate reductase (MTHFR) rs1801133 were identified only in the RNA-derived libraries of the two U2OS variants with the highest MTX resistance level. Significantly upregulated gene expression associated with development of MTX resistance was revealed for dihydrofolate reductase (DHFR), whereas SLC19A1 was downregulated. In addition, a fusion transcript of DHFR (ex4) and MutS Homolog 3 (MSH3) (ex9) was identified in the RNA-libraries derived from the two U-2OS variants with the highest MTX resistance level. This innovative mmNGS approach allowed the simultaneous exploration of SNPs at DNA and RNA level in human HGOS cell lines, providing evidence of functional involvement of allele changes associated with development of MTX resistance.